2016
DOI: 10.1002/app.44422
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous removal of Cd, Co, Cu, Mn, Ni and Zn from synthetic solutions on a hemp‐based felt: Experimental design

Abstract: International audienceThe potential of using a hemp-based material in felt form as an adsorbent for removing the metals from aqueous mixturesof Cd, Co, Cu, Mn, Ni, and Zn is investigated in the present study using batch experiments at an initial pH between 4.9 and5.2. The operating variables studied were initial metal concentration, adsorbent dosage, contact time, agitation speed, temperature,presence of NaCl, and pH. Experiments showed that this nonconventional adsorbent exhibited interesting capacities: 1 g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 40 publications
2
33
0
Order By: Relevance
“…Adsorption experiments showed that these nonconventional adsorbents exhibited high adsorption capacities. Scanning electron microscopy and energy‐dispersive X‐ray spectroscopy studies confirmed changes in the morphology of the materials after adsorption and demonstrated the adsorption mechanism . To our knowledge, this was the first report on the removal of metals from polycontaminated aqueous solutions by hemp‐based materials in the form of felt.…”
Section: Introductionmentioning
confidence: 57%
See 4 more Smart Citations
“…Adsorption experiments showed that these nonconventional adsorbents exhibited high adsorption capacities. Scanning electron microscopy and energy‐dispersive X‐ray spectroscopy studies confirmed changes in the morphology of the materials after adsorption and demonstrated the adsorption mechanism . To our knowledge, this was the first report on the removal of metals from polycontaminated aqueous solutions by hemp‐based materials in the form of felt.…”
Section: Introductionmentioning
confidence: 57%
“…This figure clearly shows that the activated HEMPM is more efficient than the nonmodified material, whatever the metal considered, pointing out the important role of the carboxylic groups coated in the felt. These groups are responsible for metal ion binding through electrostatic interactions and ion exchange, and their presence in HEMPM positively influenced its performance. In Figure , the average values of Ni concentrations decrease significantly after treatment: HEMPM was more efficient than HEMP, whatever the DW treated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations